Accounting Conservatism as a Protective Mechanism: Exploring Its Impact on the Relationship Between Financial Decisions and Likelihood of Financial Distress among Listed Firms in Kenya - Maiyo, Rodgers; Cheboi, Josephat; Limo, Patrick (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose- This study investigates the moderating role of accounting conservatism in the relationship between corporate financial decisions (financial leverage, investment rate, and dividend payout policy) and the likelihood of financial distress among firms listed on the Kenyan Securities Exchange.Design/Methodology- The study analyzed a sample of 45 firms over 14 years from 2008 to 2021, resulting in 630 firm-year observations. Panel logistic regression was employed to assess secondary data from annual financial reports.Findings- Results reveal that financial leverage and investment rate significantly increase financial distress risk, while dividend payout policy has a negative effect. Accounting conservatism moderates these relationships by reducing the impact of financial leverage and enhancing the effect of dividend policy.Practical Implications- Managers should implement conservative accounting practices to align incentives with long-term shareholder interests, ensuring prudent financial reporting and minimizing financial distress risks. Originality- This research contributes to the understanding of financial decisions and distress, offering insights into the role of accounting conservatism in promoting corporate financial stability.